A multifactorial interdisciplinary intervention to prevent functional and mobility decline for more participation in (pre-)frail community-dwelling older adults (PromeTheus): study protocol for a multicenter randomized controlled trial - Werner, Christian; Wolf-Belala, Nacera; Nerz, Corinna; Abel, Bastian; Braun, Tobias; Grüneberg, Christian; Thiel, Christian; Büchele, Gisela; Muche, Reiner; Hendlmeier, Ingrid; Schäufele, Martina; Dams, Judith; et al. (BMC geriatrics, 2022)
Age-related decline in physical capacity can lead to frailty, associated with an increased vulnerability to adverse health outcomes and greater healthcare utilization. In an aging population, effective strategies to prevent physical decline and frailty, and preserve independence are needed. Prevention programs for vulnerable community-dwelling older adults are, however, often not yet established and implemented in routine practice. Research on the feasibility, implementation, and (cost-)effectiveness of multifactorial, interdisciplinary intervention programs that take advantage of available services of healthcare providers is also limited. The main aim of this study is to evaluate the effectiveness of such an intervention program (PromeTheus) to prevent functional and mobility decline for more participation in community-dwelling (pre-)frail older adults.